2014
DOI: 10.1097/dbp.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

PLAY Project Home Consultation Intervention Program for Young Children With Autism Spectrum Disorders

Abstract: Objective To evaluate the effectiveness of the PLAY Project Home Consultation (PLAY) model, in combination with usual community services (CS), to improve parent-child interaction, child development, and autism symptomatology in young children with autism spectrum disorders (ASD) compared to CS only. Methods Children (N=128) with autism or PDD-NOS (DSM IV criteria), 2 years-8 months to 5 years-11 months, recruited from five disability agencies in four U.S. states, were randomized in two one-year cohorts. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(172 citation statements)
references
References 43 publications
7
155
0
10
Order By: Relevance
“…They showed that activities related to MT facilitate social communication and dynamic, common, and active interaction in children with autism. Our results with training using PT was found to be consistent with the research conducted by Solomon et al (2014); Gutman et al (2012);and Rodrigues, Sei, and Arruda (2013). They showed that playing intervention programs increases interaction and language development in children with autism.…”
Section: Discussionsupporting
confidence: 82%
“…They showed that activities related to MT facilitate social communication and dynamic, common, and active interaction in children with autism. Our results with training using PT was found to be consistent with the research conducted by Solomon et al (2014); Gutman et al (2012);and Rodrigues, Sei, and Arruda (2013). They showed that playing intervention programs increases interaction and language development in children with autism.…”
Section: Discussionsupporting
confidence: 82%
“…Two RCTs identified effects on parent responsivity in a parent coaching condition, compared to a treatment-as-usual group (Solomon, Van Egeren, Mahoney, Quon Huber, & Zimmerman, 2014) or parent advocacy control group (Siller, Hutman, & Sigman, 2013), even when coaching occurred only once monthly for 12 months (similar to Drew et al, 2002) (Solomon et al, 2014) or once weekly for 12 weeks (Siller et al, 2013). In a 1-year follow-up of participants in Solomon et al’s (2014) sample, the lack of child treatment effects persisted (Oosterling et al, 2010). In Siller et al’s (2013) study, children in the parent coaching group having baseline expressive language skills below the 12-month level showed greater expressive language gains compared to controls 1 year later, at follow-up.…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%
“…Further, responsive caregiver behavior correlated with positive child outcomes (Casenhiser et al, 2013). In another RCT of an intervention based on Floortime, Solomon et al (2014) evaluated the Play and Language for Autistic Youngsters (PLAY) program, which included monthly home consultation with parents. Children in the PLAY group showed significant improvements in ASD classification, social-emotional skills, and quality of parent-child interactions but not ASD symptoms, communication skills, or development level.…”
Section: Dsp Parent Trainingmentioning
confidence: 99%